Leads in Arctic pack ice enable early phytoplankton blooms below snow-covered sea ic - Assmy, Philipp; Fernández-Méndez, Mar; Duarte, Pedro; Meyer, Amelie; Randelhoff, Achim; Mundy, Christopher John; Olsen, Lasse; Kauko, Hanna M.; Bailey, Allison; Chierici, Melissa; Cohen, Lana; Doulgeris, Anthony Paul; et al. (Scientific Reports, 2017)
Source at http://dx.doi.org/10.1038/srep40850 The Arctic icescape is rapidly transforming from a thicker multiyear ice cover to a thinner and largely seasonal first-year ice cover with significant consequences for Arctic primary production. One critical challenge is to understand how productivity will change within the next decades. Recent studies have reported extensive phytoplankton blooms beneath ponded sea ice during summer, indicating that satellite-based Arctic annual primary production estimates may be significantly underestimated. Here we present a unique time-series of a phytoplankton spring bloom observed beneath snow-covered Arctic pack ice. The bloom, dominated by the haptophyte algae Phaeocystis pouchetii , caused near depletion of the surface nitrate inventory and a decline in dissolved inorganic carbon by 16 ± 6 g C m − 2 . Ocean circulation characteristics in the area indicated that the bloom developed in situ despite the snow-covered sea ice. Leads in the dynamic ice cover provided added sunlight necessary to initiate and sustain the bloom. Phytoplankton blooms beneath snow-covered ice might become more common and widespread in the future Arctic Ocean with frequent lead formation due to thinner and more dynamic sea ice despite projected increases in high-Arctic snowfall. This could alter productivity, marine food webs and carbon sequestration in the Arctic Ocean